Managing Hyperosmotic Stress through Phase Separation. Issue 9 (September 2020) - Peran, Ivan; Sabri, Nafiseh; Mittag, Tanja
Abstract : In a recent study, Yasuda et al. show how liquid–liquid phase separation (LLPS) under hyperosmotic stress conditions allows cells to react to ubiquitinated proteins and to assemble nuclear, liquid compartments that recruit proteasomes and result in aggregate clearance.